Diversification of competitive results of the food industry of the ʻoldʼ and ʻnewʼ EU countries - Łukiewska, Katarzyna (Zróżnicowanie wyników konkurencyjnych przemysłu spożywczego krajów ,,starej” i ,,nowej” UE, 2020)
The purpose of this elaboration was to evaluate the diversity of competitive results of the food industry in the ‘old’ and ‘new’ EU countries in 2004, 2011 and 2018. The indicators of export market share, trade coverage and revealed comparative advantages of the food industry were used. Next the chosen descriptive statistics (arithmetic mean, coefficient of variation, lower and upper quartile, median, range, interquartile range), the box-plot figures and the Mann-Whitney U test, were applied. The conducted research proved the visible disparities between the ‘old’ and ‘new’ EU members in the range of all the evaluated indicators of competitive position, mainly in the case of export market share. The evaluation of the competitive results in the selected years demonstrate that there is a gradual process of reducing the gap within the competitive position of the food industry of the ‘old’ and ‘new’ countries of the EU
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 4, s. 115-126
Keywords: competitiveness; export share; trade balance; comperative advantages; food industry; konkurencyjność; udział w eksporcie; bilans handlowy; przewagi komparatywne; przemysł spożywczy